Analyzing Brand Awareness Of Harley Davidson Shop A Case Study Of PT. Siliwangi Harley Davidson Bandung - Wardhana, Sokha; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2021)
Marketing strategy has an important role in a company. Marketing Strategy is a marketing mindset that will be used to achieve its marketing goals. Likewise at PT. Siliwangi Harley Davidson, marketing strategy is very important to create brand awareness to support product sales. This study uses qualitative research which is phenomenological method. In-depth interviews uses to get the deep information about marketing of PT. Siliwangi Harley Davidson from the informants.The result of textural analysis show that PT. Siliwangi Harley Davidson has done four marketing strategies which are event marketing strategy, offline marketing strategy, social marketing strategy, referral marketing strategy, and SEO marketing strategy. They haven’t done two more marketing strategies which are inbound marketing strategy and email marketing strategy.Background:This study aims to give the best marketing strategies of PT. Siliwangi Harley Davidson in order to increase the brand awareness of PT. Siliwangi Harley Davidson especially in West Java as their target market.Methodology:This study uses qualitative research which is phenomenological method. Validate using intersubjectivity method.Results: The result of the study show that PT. Siliwangi Harley Davidson has done four marketing strategies which are event marketing strategy, offline marketing strategy, social marketing strategy, referral marketing strategy, and SEO marketing strategy. They haven’t done two more marketing strategies which are inbound marketing strategy and email marketing strategy.Conclusion: PT. Siliwangi Harley Davidson should applicate the seven marketing strategies in West Java in order to increase the brand awareness in West Java itself.PT. Siliwangi Harley Davidson also need to pay attention of the SWOT analysis, and including the TOWS analysis for making the best marketing strategies.Keywords: Marketing Strategy, Harley Davidson, Brand Awareness,SWOT Analysis,TOWS Matrix,Qualitative Method.